2010
DOI: 10.1111/j.1447-0349.2009.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Home‐visit nurses' attitudes for providing effective assistance to clients with schizophrenia

Abstract: There were two objectives of this study. The first was to identify the attitudes of home-visit nurses towards clients with schizophrenia that lead to the provisions of effective care and positive client outcomes for clients with schizophrenia. The second was to develop a framework to understand how nurses acquire nursing attitudes that lead to such provisions. Seven expert home-visit nurses who had successfully prevented rehospitalization of clients with schizophrenia for more than 2 years were interviewed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 23 publications
(40 reference statements)
3
20
0
Order By: Relevance
“…Nursing practice in HC is influenced both by patient profile and by the logic peculiar to homes. In HC, nurses offer care to a diverse profile, with a predominance of patients under palliative care (12)(13)22,27,33,50,52,55) and the elderly (16,(28)(29)35) being noticed in this review, although analyzed articles have also reported care actions for children (11,19,25) and young individuals (28) with complex needs, as well as mentally challenged persons (14,27) . Review of the articles revealed that nurses conduct various actions in HC, such as: interpersonal support; health education for patients, family members; and caregivers; performance of technical procedures; and clinical and administrative supervision, as demonstrated in Chart 1.…”
Section: Nursing Actions In Home Carementioning
confidence: 98%
See 4 more Smart Citations
“…Nursing practice in HC is influenced both by patient profile and by the logic peculiar to homes. In HC, nurses offer care to a diverse profile, with a predominance of patients under palliative care (12)(13)22,27,33,50,52,55) and the elderly (16,(28)(29)35) being noticed in this review, although analyzed articles have also reported care actions for children (11,19,25) and young individuals (28) with complex needs, as well as mentally challenged persons (14,27) . Review of the articles revealed that nurses conduct various actions in HC, such as: interpersonal support; health education for patients, family members; and caregivers; performance of technical procedures; and clinical and administrative supervision, as demonstrated in Chart 1.…”
Section: Nursing Actions In Home Carementioning
confidence: 98%
“…Relationship of help/Interaction (14,(17)(18)(19)(20)(24)(25)(29)(30)35,42,44,46,(48)(49)54) Emotional, mental, or psychological support (37,40,42,46,51,55) Communication (12,18,21,51,56) Relationship of trust (10,22,26,42,56) Negotiation (16,21,26,52) Respect (11,41,56) Dialog (20,26) and listening (18) Educational actions Guidelines for families, caregivers, and/or patients (13,19,25,27,29,32,36-40,44-46, 48,51,53) Development of teaching strategies (48) Learning about social resources (51) Training of patients, family, and neighbor network and other sectors for risk prevention in emergencies (38) Guidelines for other nurses (40) Care actions Medication management or infusion …”
Section: Interactive Actionsmentioning
confidence: 99%
See 3 more Smart Citations